2014
DOI: 10.1080/01904167.2014.888740
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Concentration, Sugar Content and Yield of Iranian ‘Khatooni’ Melon Affected by Grafting, Pruning and Thinning

Abstract: 2 Macroelements in leaves and fruits, sugar of fruits, and yield of 'Khatooni' melon were compared with melons grafted onto rootstocks cvs. 'Ace ', 'Shintozwa', and 'ShintoHongto', and trained into three methods: T1) no pinching and fruit thinning; T2) pinched to produce two lateral branches; and T3) pinched to two branches and all flowers and lateral branches from lower nodes thinned. Concentrations of nitrogen (N), phosphorus (P), and potassium (K) increased in leaves onto 'Shintozwa', whereas opposite trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…For example, grafting mini watermelon ‘Ingrid’ onto the interspecific pumpkin hybrid ‘PS1313’ increased K and Mg concentrations in the pulp 111 . Additionally, melon cultivar ‘Khatooni’ grafted onto ‘Ace’ and ‘Shintoza’ rootstocks showed increased N, P and K concentrations 112 . According to Consentino et al 113 .…”
Section: Grafting and Its Influence On Plant Qualitative Profilementioning
confidence: 99%
See 1 more Smart Citation
“…For example, grafting mini watermelon ‘Ingrid’ onto the interspecific pumpkin hybrid ‘PS1313’ increased K and Mg concentrations in the pulp 111 . Additionally, melon cultivar ‘Khatooni’ grafted onto ‘Ace’ and ‘Shintoza’ rootstocks showed increased N, P and K concentrations 112 . According to Consentino et al 113 .…”
Section: Grafting and Its Influence On Plant Qualitative Profilementioning
confidence: 99%
“…111 Additionally, melon cultivar 'Khatooni' grafted onto 'Ace' and 'Shintoza' rootstocks showed increased N, P and K concentrations. 112 According to Consentino et al 113 grafting of 'Birgah' eggplant onto Solanum torvum rootstock significantly increased protein, K, Fe and Zn content by 22.9, 7.2, 20.0 and 2.4%, respectively, compared to non-grafted plants. Furthermore, tomato fruits' 'Big Red' grafted onto 'Heman' had higher Ca contents as a result of improved water and nutrient uptake from the rootstock's vigorous root system.…”
Section: Grafting and Its Influence On Plant Qualitative Profilementioning
confidence: 99%
“…These authors observed that the phosphorus (P) and Mg contents of fruit grafted on to 'Shintosa' were lower than those grafted on to C. melo rootstocks or non-grafted melons. In fruit of 'Khatooni', nitrogen (N), P and K were higher in fruit from plants grafted on to ' Ace' or 'Shintoza' (Salehi et al, 2014). Khah et al (2006) investigated the mineral content of tomato fruits from 'Big Red' grafted on to hybrid rootstocks 'Heman' and 'Primavera'.…”
Section: Mineralsmentioning
confidence: 99%
“…In protected cultivation system, sowing of some summer vegetable such as cucumber, melon, watermelon, tomato, pepper, and bell pepper is practiced in winter Fusarium tolerance Improves availability of N, P, Ca, K, Mg, Mn, and Zn to the scion. Reduces uptake and transport of Na and heavy metals to the scion Low and high temperature tolerant, vigorous root system, salt tolerant Ruiz et al, 1997;Lee et al, 2010;Bautista et al, 2011;Salehi et al, 2014 Keumsakwa Gu et al, 2008;Lee et al, 2010 Butternut, Unyong #1, Super Unyong, PPMR-1 (Cucurbita moschata Duch. )…”
Section: No Report Available Needs Investigationsmentioning
confidence: 99%